Penguatan MBKM Melalui Revitalisasi Kurikulum Berbasis Outcome Based Education Pada Program Studi Manajemen Pendidikan Islam - Rodin, Rhoni; Warsah, Idi; Warlizasusi, Jumira; Adisel (El-Idare, 2024)
This study aims to identify strategies for revitalizing an Outcome-Based Education (OBE)-based curriculum to support the strengthened implementation of Merdeka Belajar Kampus Merdeka (MBKM) in the Islamic Education Management (MPI) Study Program. The study evaluates the impact of revitalization on improving the quality of learning, aligning graduates with labor market needs, and optimizing MBKM activities. Using qualitative methods and a library research approach, the research analyzes government policies, scholarly literature, and other relevant documents. Data analysis follows the stages outlined by Miles and Huberman, including data collection, reduction, and conclusion drawing. The findings indicate that the synergy between OBE and MBKM can enhance the relevance of the MPI study program curriculum to workforce demands through the design of measurable and relevant learning outcomes. This revitalization requires curriculum redesign, strengthening faculty competencies, and collaboration with external partners. The study provides strategic recommendations for MPI program managers in designing adaptive and relevant curricula while contributing to the advancement of Islamic education management science.